2021
DOI: 10.3390/ma14051182
|View full text |Cite
|
Sign up to set email alerts
|

PICN Nanocomposite as Dental CAD/CAM Block Comparable to Human Tooth in Terms of Hardness and Flexural Modulus

Abstract: Polymer infiltrated ceramic network (PICN) composites are an increasingly popular dental restorative material that offer mechanical biocompatibility with human enamel. This study aimed to develop a novel PICN composite as a computer-aided design and computer-aided manufacturing (CAD/CAM) block for dental applications. Several PICN composites were prepared under varying conditions via the sintering of a green body prepared from a silica-containing precursor solution, followed by resin infiltration. The flexural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
(19 reference statements)
0
24
0
Order By: Relevance
“…Such PICN structure provides unique mechanical properties including machinability. In fact, the mechanical properties of the PICN composite, such as hardness and elastic modulus, are reportedly similar to that of enamel and dentin rather than those of conventional resin composite 13,15) . From a materials science perspective, a key factor for mimicking the enamel properties is the microstructure; thus, the PICN structure contributes to mimicking the unique machinability of enamel.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Such PICN structure provides unique mechanical properties including machinability. In fact, the mechanical properties of the PICN composite, such as hardness and elastic modulus, are reportedly similar to that of enamel and dentin rather than those of conventional resin composite 13,15) . From a materials science perspective, a key factor for mimicking the enamel properties is the microstructure; thus, the PICN structure contributes to mimicking the unique machinability of enamel.…”
Section: Discussionmentioning
confidence: 89%
“…The present PICN model teeth were formed in the steps which involved the precursor slurry casting to the tooth-shaped mold followed by light curing. This light-curable precursor slurry was prepared as indicated in our previous studies 13,14) . The slurry contains silica nanoparticles, alcohol solvents (PrOH and POE), resin monomers (HEMA and TEGDMA), and the photo-initiator (BAPO).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical composition of the precursor slurry used in this study was slightly modified from the PICN composite used with CAD/CAM blocks reported in our previous study (Kawajiri et al 2021). The present composition contained a high silica loading (49.5 wt%) and exhibited excellent printing ability.…”
Section: Discussionmentioning
confidence: 99%